Organizational resource perception and teachers’ digital competence in higher education: The mediating role of teacher agency - Huo, Kang; Chen, Peng-Fei (Edelweiss Applied Science and Technology, 2025)
With the rapid development of educational informatization, teachers’ digital competence in higher education has become a crucial capacity for advancing teaching innovation and educational reform. This study aims to examine how university teachers’ perceptions of organizational resources influence their digital competence, with particular emphasis on the mediating role of teacher agency. A quantitative cross-sectional survey was conducted with 813 valid responses from teachers in five universities in Shanxi Province, China. Regression and mediation analyses were performed using the PROCESS macro for SPSS, controlling for gender and age. The results indicate that perceptions of organizational resources significantly and positively predict teachers’ digital competence, and teacher agency partially mediates this relationship, with resources exerting both direct and indirect effects through enhanced self-efficacy and proactive engagement. These findings underscore the importance of supportive institutional resources and proactive teacher agency in fostering digital competence. This study contributes theoretically by extending teacher agency research within technology integration and provides practical implications for universities seeking to strengthen training, infrastructure, and motivational support.